9t-3=-7+7t

Simple and best practice solution for 9t-3=-7+7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t-3=-7+7t equation:



9t-3=-7+7t
We move all terms to the left:
9t-3-(-7+7t)=0
We add all the numbers together, and all the variables
9t-(7t-7)-3=0
We get rid of parentheses
9t-7t+7-3=0
We add all the numbers together, and all the variables
2t+4=0
We move all terms containing t to the left, all other terms to the right
2t=-4
t=-4/2
t=-2

See similar equations:

| 10+8w=9w | | r-257=66 | | (x-3)²-(3-x)²=1 | | 63=8y-52.8 | | 5(x+1)=-6 | | 6+2b=b | | 490-56=x6 | | t-378=603 | | (7x-2)=(4x+9)+(2x+6) | | 2.3n-13.8=-10.5n+9.16-3.6n | | h/18=21 | | -9k=-9-10k | | 7.50x-6.25=26.25 | | 434=6x | | 8+12u=10u | | 20+12p-18p=-10-3p | | h+1=100 | | 7x+2(4–2x)=-25+6 | | 7(v+6)=7v+12 | | -7+15k=13k-15 | | 8-7s=-8s-2 | | k+11=98 | | 6.25x-7.50=26.25 | | -3x-5-x+3=-2(2x+3) | | 17.5=17.4y-0.36 | | 7(x+1)=7x+9 | | g-16=39 | | -129=f+11 | | 5x-6=2x-20 | | -11t-11=15-13t-2 | | 7(z+2)=7z-6 | | 2x+57=-57 |

Equations solver categories